2022
DOI: 10.9734/arrb/2022/v37i330496
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of Albino Rats Orally Administered with Honey from Apis mellifera adansonii and Refined Sugar at Varying Levels

Abstract: The purpose of this research was to find out the growth performance of albino rats orally administered with honey from Apis mellifera adansonii and refined granulated sugar at varying quantities. Twenty-five (25) healthy albino rats used in the study were grouped into five treatments based on the dose of natural honey and granulated sugar as follow: T1 (1.02g of honey kg BW), T2 (1.40g of honey kg BW), T3 (1.02g of granulated sugar kg BW), and T4 (1.40g of granulated sugar kg BW). However, rats in T5 were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This finding supports the report by Bobiş et al [27] who reported that honey may provide nutritional benefits in the management of diabetes mellitus. This also supports the observation by Adekanmbi et al [11] who reported that honey is rich in fructose, glucose, and minerals such as magnesium, potassium, calcium, phosphate, sulphur, ferrous, and sodium chloride as well as vitamins such as B1, B2, B5, B6, and C. As a result of the rich nutrients in honey, Ononye et al [28] also reported that natural honey should be consumed regularly by humans for efficient performance of the body.…”
Section: Discussionsupporting
confidence: 89%
“…This finding supports the report by Bobiş et al [27] who reported that honey may provide nutritional benefits in the management of diabetes mellitus. This also supports the observation by Adekanmbi et al [11] who reported that honey is rich in fructose, glucose, and minerals such as magnesium, potassium, calcium, phosphate, sulphur, ferrous, and sodium chloride as well as vitamins such as B1, B2, B5, B6, and C. As a result of the rich nutrients in honey, Ononye et al [28] also reported that natural honey should be consumed regularly by humans for efficient performance of the body.…”
Section: Discussionsupporting
confidence: 89%